Dermal Triangular Flaps to Prevent Pseudoptosis in Mastopexy Surgery: The Hammock Technique. Issue 11 (November 2019) - Watfa, William; Zaugg, Patrice; Baudoin, Julien; Bramhall, Russell J.; Raffoul, Wassim; di Summa, Pietro G.
Abstract : Background: Mastopexy is one of the most performed cosmetic surgery procedures in the United States. Despite the numerous mastopexy techniques that were published in the past decades, preventing pseudoptosis to ensure longer lasting results remains the principal challenge. Objectives: This paper describes a new mastopexy technique developed for moderate to severe ptosis/pseudoptosis associated with upper pole deflation. Considering some of the commonest risk factors generally considered predictive of worse outcomes (massive weight loss, multiple pregnancies, skin quality, smoking, age), we aimed to assess whether this technique could be beneficial in the support of the desired breast shape over time. Methods: Twelve patients, all featuring 1 or more of the abovementioned preoperative risk factors, were operated on by the same senior surgeon with the hammock mastopexy technique using dermal flaps as a support for the glandular reshaping (6 bilateral mastopexies and 6 unilateral mastopexies for contralateral symmetrization after breast reconstruction). Patients' characteristics, such as smoking, weight loss, or multiparity with consequent inelastic skin, age, and lengthy nipple–areola complex lift, were considered as independent risk factors for ptosis recurrence and bottoming out. Patients were divided into 3 subgroups according to the number of their risk factors. Aesthetic results were assessed at 12 months postoperatively. Changes in postoperative were assessed for each patient by breast measurements and a superposition of the standardized breast photographs. Long-term outcomes were compared with a control group of 6 patients who benefited from mastopexy without "hammock technique." Results: Satisfactory maintenance of shape and stable nipple–areola complex position was seen at 12 months regardless of the number of risk factors. However, a statistically significant difference was found in lower pole lengthening between patients with more than 3 risk factors compared to other groups. Aesthetic measurement results were consistent between the patient and surgeon reporting a satisfying cosmetic result, regardless of the number of risk factors. In the control group, we found a significant increase in breast lower pole measurements at 12 months when compared with the hammock group. Conclusions: This mastopexy technique improves projection and reinforces the lower pole support with lateral and medial dermal flaps. The technique is safe and reliable and provides easily reproducible results for patients with risk factors for postoperative pseudoptosis. Abstract : Supplemental Digital Content is available in the text.